New Imaging Approaches to Pheochromocytomas and Paragangliomas - Havekes, Bas (2009)
Formerly used concepts for pheochromocytomas and paragangliomas have been challenged by recent discoveries that a) at least 24% of tumors are familial and thereby often multiple in various locations throughout the body, b) tumors are often malignant and perhaps more aggressive if associated with SDHB gene mutations, c) clinically silent tumors may present only with dopamine hypersecretion, d) tumors are more often found as incidentalomas in the current era where CT and MRI are more commonly used and e) MRI may be less specific for pheochromocytoma and paraganglioma than previously thought. Because of unique tumor characteristics (e.g. the presence of cell membrane and intracellular vesicular norepinephrine transporters) these tumors were ‘born’ to be imaged by means of specific functional imaging approaches. Moreover, additional recent discoveries related to apoptosis, hypoxia, acidosis, anaerobic glycolysis, and angiogenesis, often disturbed in tumor cells, open new options and challenges to specifically image pheochromocytomas and paragangliomas and possibly link those results to their pathophysiology, genotypic alterations and metastatic potential. Functional imaging, especially represented by PET, offers an excellent approach by which tumor specific processes can be detected, evaluated and seen in the context of tumor-specific behavior and its genetic signature. In this review, we address the recent developments in new functional imaging modalities for pheochromocytoma and paraganglioma and provide the reader with a new modified imaging algorithm for various pheochromocytomas and paragangliomas of sympathetic origin. Current imaging algorithms of head and neck parasympathetic paragangliomas are not discussed. Finally, this review outlines some future perspectives of functional imaging of these tumors.